The Influence of E-Service Quality and Price Fairness on E-Loyalty through E-Satisfaction among Shopee Sellers - Cindy, Vera Deyana; Parlyna, Ryna; Kasofi, Adnan; Munawaroh (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2026)
Due to the swift expansion of e-commerce in Indonesia, Shopee has become the most dominant marketplace. However, Shopee faces strategic difficulties in retaining seller loyalty due to the rise of new rival, especially with regard to thoughts about administrative costs and the standards of services provided. This study uses the theory of S-O-R to examine price fairness and e-service quality influence on Shopee sellers' e-loyalty through e-satisfaction as a mediating variable. Using a judgmental sampling approach, 205 Shopee sellers that run businesses in the Greater Jakarta region and have been actively selling during the last six months represent the study's sample. A six-point Likert scale questionnaire was used to gather the data, and Microsoft Excel and SmartPLS 4 were used for analysis. The findings indicate that e-service quality positively and significantly influenced e-satisfaction and e-loyalty. Price fairness, on the other hand, positively and significantly affects e-satisfaction but has insignificant influence on e-loyalty. Moreover, e-satisfaction positively and significantly influenced e-loyalty. E-satisfaction indirectly mediates the relationship between price fairness and e-loyalty, but not the relationship between e-service quality and e-loyalty.